GST-tag Affinity Chromatography: A Technique for Outstanding Results from the Purification of Recombinant Proteins - Md Asaduzzaman; Lutfun Nahar (Innovations in Biological Science Vol. 5, 2024)
In the sphere of fundamental biological research, affinity tags have been used as potentially useful instruments, particularly for the synthesis of recombinant proteins and functional proteomics. These affinity tags were widely used to make the differentiation of protein complexes and the purification of recombinant proteins easier. Affinity chromatography has made substantial use of glutathione-S-Transferase (GST) tag for fusion/recombinant protein purification, protein-protein interaction research, and the production of medicinal products. In this review, we describe the advantage of GST-tag in affinity chromatography technique as a method for inducible, high-level protein expression and purification of recombinant protein. A recombinant protein is a protein which is expressed in pGEX or pET vectors and that protein with GST-tag encoded at the NH2 - or COOH- region of genome sequence. There are some expression vectors which has different sites to approve for unidirectional insertion of the coding region DNA, promoter, primers, antibiotic, Ori and GST-tag into pGEX vectors. Reduced glutathione (GSH) is utilized in affinity chromatography to elute and store the GST-tag containing recombinant protein. The recombinant protein’s GST tag is removed for digestion using a protease enzyme, and the protein is then purified using a different affinity approach.